PROTOTYPE OF VACUUM FRYING OYSTER MUSHROOM CHIPS - Anisa Nabillah; Selastia Yuliati; Mustain Zamhari (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2022)
Oyster mushroom is plant that is quite easy to cultivate because it only requires growing media for oyster mushrooms, oyster mushroom seeds and a humid place for cultivation. Oyster mushroom is a type of plant that is fibrous and contains a lot of water causing the shelf life of oyster mushrooms after harvest is very short. To increase the economic value of oyster mushrooms, it is necessary to process oyster mushrooms into something so that processed oyster mushrooms have a long shelf life, namely by processing oyster mushrooms into chips, but the manufacture of oyster mushroom chips still uses conventional or manual methods so that the quality of the resulting chips is still not good. By using innovative technology through a prototype design tool with the vacuum frying method, it produces chips that are of higher quality than conventional frying methods which are seen from the water content contained in oyster mushroom chips, which is less than 1% with an evaporated water content of 80%. The prototype of this vacuum frying fryer has an overall volume of 260,000 cm3 with an overall length of 100 cm, a width of 40 cm and a height of 65 cm and uses an electric motor of 2461.76 watts or 3.3012 HP